Experimental demonstration of modified constant modulus algorithm with polarization demultiplexing in Stokes space in optical coherent receiver - Huang, Bohang; Dong, Xiangyong; Shi, Fengjie; Yu, Zhenming; Xu, Kun (Optics communications, 2025)
Constant modulus algorithm (CMA) is widely applied for polarization demultiplexing in coherent optical communication system. However, the singular value problem always plagues CMA. Modified CMA based on polarization demultiplexing in Stokes space (SS-PDM) was proposed to avoid the singular value problem in simulation. Here we firstly experimentally demonstrate the modified CMA based on SS-PDM in optical coherent receivers. We conduct experiment of 40-Gbit/s polarization multiplexing (PDM) QPSK to verify this method. The experimental results show that the singularity problem of CMA disappears for Polarization-dependent loss (PDL) of 2.7 dB and 4.8 dB by using the modified CMA and the convergence speed of the modified CMA increases significantly compared with that of conventional CMA.